Structure and Function Relationship in Prolyl Oligopeptidase - Van Elzen, Roos; Lambeir, Anne-Marie (CNS & Neurological Disorders - Drug Targets, 2011)
Prolyl oligopeptidase (POP) belongs to a unique class of serine proteases. Based on extensive enzyme kinetic measurements it has become clear that POP acts in a multifaceted way. This is reflected in the complex behavior in different reaction conditions with different substrates. Also the typical structural architecture of POP, with the active site located at the interface of the catalytic domain and the β-propeller domain, has instigated many researchers to speculate about the mechanism of functioning. The latest developments support the idea of extended conformational changes upon substrate binding. In this review the plethora of available information is assembled into a coherent and stepwise description of the structural composition of POP. In one aspect the composition and contribution of structural boundaries at the active site are described. Attention is focused on the catalytic components and the features that are presumed to confine the substrate specificity. Complementary to this, the specificity of POP towards the residues surrounding the scissile bond is described by means of a consecutive evaluation of the preferred physico-chemical properties. Together, these two approaches may facilitate a better understanding of the concepts that determine catalytic behavior of POP in physiological conditions.
Keywords: peptidase